Peran Tradisi Lokal dalam Pembentukan Kurikulum Pendidikan Indonesia - Zahrotul Mukarromah; Indah Fatma Maulidiyah; Sarah Azka Fidaroin (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to analyze the role of local traditional in shaping the educational curriculum in Indonesia. In the current context of globalization, the value of local traditions is increasingly important for maintaining the nation’s cultural identity and enriching the learning process. This study used qualitative methods, including literature review and descriptive analysis of existing educational policies and the implementation practices of local wisdom-based curricula in Indonesia. The results indicate that local traditions play a significant role in building student character, strengthening national identity, and creating situational and relevant learning. However, challenges remain in the process of integrating local traditions into the national curriculum, such as limited resources, differences in cultural interpretation, and a lack of teacher training. Therefore, a structured and collaborative strategy is needed between the government, schools, and communities to optimize the role of local traditions in education.